diff --git a/misc/she/memo.txt b/misc/she/memo.txt index 5ee1709..8c40b78 100644 --- a/misc/she/memo.txt +++ b/misc/she/memo.txt @@ -31,18 +31,46 @@ Bi := d Pi - h Ai verify h = Hash(P2, A1, A2, B1, B2) ----------------------------------------------------------------------------- CipherTextGT -P ; generator of GT +P ; generator of GT, GT=

x1, x2 ; secrect key (P0, P1, P2, P3) := (P, x1 P, x2 P, x1 x2 P) ; public information CipherText c = (A0, A1, A2, A3) dec(c) = 0 <=> A0 = x2 A1 + x1 A2 - x1 x2 A3 ; (*) -construction of ZKP for dec(c) = 0, i.e., show (*) +F(a1, a2, a3) := a2 A1 + a1 A2 - a3 A3 + +dec(c) = 0 <=> A0 = F(x1, x2, x1 x2) + +Sigma-protocol for dec(c) = 0, i.e., show (*) + +Prover: + b1, b2, b3 ; rand + Bi := bi P (i = 1, 2, 3) + X := F(b1, b2, b3) + send (B1, B2, B3, X) to Verfier + +Verifier: + takes h randomly and send to Prover + +Prover: + d1 := b1 + h x1 + d2 := b2 + h x2 + d3 := b3 + h x1 x2 + send (d1, d2, d3) to Verifier + +Verifier: + verify + di P = Bi + h Pi (i = 1, 2, 3) + X = F(d1, d2, d3) - h A0 + and accept it + +Fiat-Shamir transform: + Prover: b1, b2, b3 ; random value -Bi := bi P for i = 1, 2, 3 -X := b1 A2 + b2 A1 - b3 A3 +Bi := bi P (i = 1, 2, 3) +X := F(b1, b2, b3) h := Hash(P0, ..., P3, A0, ..., A3, B1, B2, B3, X) d1 := b1 + h x1 d2 := b2 + h x2 @@ -52,7 +80,7 @@ pi := (d1, d2, d3, h) Verifier: (pi, {Pi}, {Ai}) given Bi' := di P - h Pi for i = 1, 2, 3 -X' := d1 A2 + d2 A1 - d3 A3 - h A0 +X' := F(d1, d2, d3) - h A0 verify Hash({Pi}, {Ai}, {Bi'}, X') = h Completeness @@ -60,8 +88,10 @@ Completeness B1' = d1 P - h P1 = (b1 + h x1) P - h x1 P = b1 P = B1 B2' = d2 P - h P2 = (b2 + h x2) P - h x2 P = b2 P = B2 B3' = d3 P - h P3 = (b3 + h x1 x2) P - h x1 x2 P = B3 -X' = (b1 + h x1) A2 + (b2 + h x2) A1 - (b3 + h x1 x2)A3 - h A0 -= b1 A2 + b2 A1 - b3 A3 + h (x1 A2 + x2 A1 - x1 x2 A3 - A0) = b1 A2 + b2 A1 - b3 A3 = X +X' = F(b1 + h x1, b2 + h x2, b3 + h x1 x2) - h A0 + = F(b1, b2, b3) + h F(x1, x2, x1 x2) - h A0 + = F(b1, b2, b3) + h (F(x1, x2, x1 x2) - A0) + = F(b1, b2, b3) = X OK Soundness @@ -80,8 +110,10 @@ B1' = d1 P - h P1 = b1 P B2' = b2 P B3' = b3 P -Y := x1 A2 + x2 A1 - x1 x2 A3 - A0 ; unknown, but it is fixed -X' = b1 A2 + b2 A1 - b3 A3 + h Y +Y := F(x1, x2, x1 x2) - A0; unknown, but it is fixed +X' = F(d1, d2, d3) - h A0 = F(b1 + h x1, b2 + h x2, b3 + h x1 x2) - h A0 + = F(b1, b2, b3) + h(F(x1, x2, x1 x2) - A0) + = F(b1, b2, b3) + h Y -Hash({Pi}, {Ai}, b1 P, b2 P, b3 P, b1 A2 + b2 A1 - b3 A3 + h Y) = h +Hash({Pi}, {Ai}, b1 P, b2 P, b3 P, F(b1, b2, b3) + h Y) = h To found {b1, b2, b3, h} to hold this equation, Y must be 0.